The Belt and Road Initiative: Implications for Infrastructure Development and Economic Integration in Eurasia - Muhammad, Abdulgaffar; Mike, Micah Ezekiel Elton; Idris, Mohammed Bello; Ishaq, Aisha Ahmad; Abdullah, Auwal Kabir (Journal of Environmental Science and Economics, 2023)
This comprehensive study presents a meticulous analysis of the Belt and Road Initiative (BRI) and its profound implications for the intricate interplay between infrastructure development and economic integration in the expansive Eurasian region. By exploring the historical context and elucidating the intricate origins of the BRI, the study sheds light on its fundamental principles and multifaceted components. Furthermore, it scrutinizes the momentous significance and vast scale of this initiative, providing a nuanced assessment of the prevailing state of infrastructure in Eurasia while elucidating the pivotal role infrastructure plays in propelling economic development. The study discerningly navigates through the myriad challenges and opportunities that arise in the pursuit of infrastructure development in the region. Moreover, it delves into the intricate fabric of economic integration in Eurasia, meticulously analyzing the dynamic impact of the BRI on trade and investment flows, and elucidates the far-reaching influence of this initiative on fostering regional economic cooperation. Additionally, the study conducts a meticulous examination of specific projects, dissecting their outcomes, and conducting an in-depth analysis of the manifold successes and challenges encountered throughout BRI projects. Drawing upon these insights, the study distills invaluable lessons learned and identifies best practices that serve as a beacon for future infrastructure development initiatives. The findings of this study furnish a comprehensive understanding of the intricate implications of the BRI on infrastructure development and economic integration in Eurasia, providing essential insights for policymakers, investors, and project implementers alike.